Sustainable land management policy to address land degradation: linking old forest management practices in Senegal with new REDD+ requirements - Dieng, Moussa; Mbow, Cheikh; Skole, David L.; Ba, Baba (Frontiers in Environmental Science, 2023)
Prior to the UN Policy framework REDD+, the Government of Senegal (GoS) initiated for many decades, important land management programs to address deforestation and land degradation which affects the country’s food production, ecosystem benefits and livelihoods. A lot of investment and policies have been implemented in various ecologies to improve tree cover and ecosystem services. Reviewing and analyzing the past and present tree recovery actions that are consistent with REDD+ policy, this paper explores the way REDD + initiative could play a role in consolidating land management strategies in non-forested area. We use a method based on the wide range of experience of the Senegalese Forest Service, forest development projects and NGOs involved in the management of natural resources and a review of seven selected forestry projects/ programs through the country, We found many opportunities for Senegal in implementing REDD + activities (e.g. tree plantation, agroforestry, bush fires management, soil erosion control, sustainable intensification, ecosystem (carbon) and socio- economic (livelihoods) services etc.). Based on the lessons learned from early land restoration and management projects, the REDD+ program could take stock from existing tools and frameworks to advance the agenda and leap in the country’s preparedness as a REDD+ country. For that, the national context dictates an expansion of REDD scope 5 (enhancement of forest carbon stock) to AFOLU and afforestation/ reforestation and trees outside of forest, which means moving REDD + from LULUCF to AFOLU. The GoS needs to address two (02) key areas: 1) the land ownership issue by pursuing the land tenure reform and integrate regulations about who has access to land, who can benefit from land use services and how the benefits sharing and carbon rights must be organized and; 2) the promotion of more engagement of local communities in forest resource management through community forestry and the sustainable practices of agriculture, forestry and agroforestry.